A mask to be enchanted: the afro-maranhense baiar and the in(corporation) on scene (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
This article proposes to articulate an analysis of the creative process of the artist Vinicius Viana in his process of visual composition, when he masks himself inspired by the bodies that dance the Tambor de Mina do Maranhão, within a process in which the union of the creative body is established and baiar for the sacred of the terreiros. The experiences shared here permeate the possible place of the body mask, in a bridge with the visuality that transits between society and the sacred, matter and the invisible, between contemporary and tradition, which timelessly relate the connection between Africa and Brazil, and that penetrate the ancestress roots of an artist's dancer and his writing.
Keywords: Body; Mask; Tambor de mina; Characterization